First-Principles Study of Charge Carrier Dynamics with Explicit Treatment of Momentum Dispersion on Si Nanowires along <211> crystallographic Directions. (13th August 2018) - Fatima,; Vogel, Jon; Inerbaev, Talgat; Oncel, Nuri; Kilin, Dmitri
ABSTRACT: The ground state structure, optical properties and charge carrier dynamics of silicon nanowire (SiNW) grown in <211> crystallographic direction is studied as a function of wavevector using density functional theory. This nanowire can be used as fundamental unit of nanoelectronic devices. The optical properties are computed under assumption of momentum conservation $Δ \vec{k} = 0$ . The on-the-fly non-adiabatic couplings for electronic degrees of freedom are obtained along the ab initio molecular dynamics nuclear trajectories, which are used as parameters for Redfield density matrix equation of motion. By investigating the photo-induced process on this nanowire, it is shown that high-energy photoexcitation relaxes to the band gap edge within 75 ps. The results of these calculations help to understand the mechanism of electron transfer process on the Si nanowire.